Group prenatal care attendance: determinants and relationship with care satisfaction - Cunningham, Shayna D. (Matern Child Health J, 2017)
INTRODUCTION: Group prenatal care results in improved birth outcomes in randomized controlled trials, and better attendance at group prenatal care visits is associated with stronger clinical effects. This paper’s objectives are to identify determinants of group prenatal care attendance, and to examine the association between proportion of prenatal care received in a group context and satisfaction with care. METHODS: We conducted a secondary data analysis of pregnant adolescents (n=547) receiving group prenatal care in New York City (2008–2012). Multivariable linear regression models were used to test associations between patient characteristics and percent of group care sessions attended, and between the proportion of prenatal care visits that occurred in a group context and care satisfaction. RESULTS: Sixty-seven groups were established. Group sizes ranged from 3 to 15 women (mean=8.16, SD=3.08); 87% of groups enrolled at least five women. Women enrolled in group prenatal care supplemented group sessions with individual care visits. However, the percent of women who attended each group session was relatively consistent, ranging from 56% to 63%. Being born outside of the United States was significantly associated with higher group session attendance rates (B[SE]=11.46 [3.46], p=0.001), and women who received a higher proportion of care in groups reported higher levels of care satisfaction (B[SE]=0.11 [0.02], p<0.001). DISCUSSION: Future research should explore alternative implementation structures to improve pregnant women’s ability to receive as much prenatal care as possible in a group setting, as well as value-based reimbursement models and other incentives to encourage more widespread adoption of group prenatal care.